Center for the Leaders of the Future - Younis, Bayan; Assaf, Esraa; Duraidi, Ruba; Tuffaha, Yasmeen (My University, 2017)
Children have a potential, but they need a support to employ their complete abilities, because the children are the leaders of the future. In Palestine, unfortunately, the support has no interest, at the same time there is no exploitation for children time to improve their skills and develop their inspiration. Nablus Governorate lacks the presence of the important place that contains education, culture, social and entertainment fields. Thus, it is suggested design a center to look after children between six to fifteen years old, these ages play a key role in their brain development. Primarily, for seeing this purpose reality, architectural, structural, mechanical, electrical and environmental for design consideration are to be satisfied. The design will be carried out in accordance with local and international standards. In this project, architectural design will focus on architectural functions, building envelope and orientation. Architectural design will include planes, elevations, sections and 3-D models. In the Structural design will be analyzed and designed with consideration for Earthquake loads, 3-D modeling and dynamics response spectrum analysis. Mechanical and environmental sections will involve H-VAC, water and piping system. In addition to that, the criteria of providing emergency exist and fire system will not be neglected. Finally, the design will include power and lighting system. All analysis and design details of the project will be submitted in a t technical report and scientifically made AutoCAD drawings.